Metoda Frobeniusa, czyli o rozwiązywaniu pewnej klasy równań różniczkowych - Wiśniewski, Damian; Żyjewski, Krzysztof (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The article is a comprehensive research paper which provides theoreticalas well as practical aspects of the Ferdinand George Frobenius method.This method is based on seeking infinite series solutions for certainclass of differential equations. It is a generalization of the power series methodand allows us to solve the differential equations at least near somesingular points.